(untitled) (Acta Scientiarum. Biological Sciences, 2010)
This study evaluated the pathogenic characteristics of bacteria isolated from Litopenaeus vannamei during an outbreak at the Laboratory of Marine Shrimp, UFSC, Santa Catarina State, Brazil. Their virulence potential in larvae and juvenile shrimp and the effects on the total haemocyte count, phenoloxidase activity and serum agglutinate titre were examined after experimental infection. Bacterial strains were isolated from larvae and adult shrimps, identified by the AP120E biochemical system as: two strains of Vibrio alginolyticus, three of Aeromonas salmonicida and one of Pasteurella multocida sp. and Pasteurella sp. All the bacterial strains isolated in this study caused mortality in shrimp. One strain of V. alginolyticus was responsible for 97.3 and 88.7% mortality in larvae and juvenil shrimps, respectively. The shrimp immunological system was influenced by experimental infection with V. alginolyticus. Decrease in the total haemocyte count and increase in the phenoloxidase activity and the serum agglutinate titre (p < 0.05) were observed. The results showed the high pathogenicity of V. alginolyticus isolated from larvae and juvenile reared marine shrimp.